The Dynamics of the Influence of Macroeconomic Factors and Capital Structure on Financial Performance and Company Size: A Study of Healthcare Companies on the IDX (2021–2024) - Widanarni Pudjiastuti (CV. Ulil Albab Corp, 2026)
This study aims to examine the influence of macroeconomic fundamental factors and capital structure on the financial performance and size of companies in the healthcare sector listed on the Indonesia Stock Exchange for the 2021–2024 period. Using a quantitative approach and the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, this study analyzes secondary data from company financial reports, Bank Indonesia, and other reliable sources to empirically test the relationship between variables. The results of the bootstrapping analysis indicate that all hypotheses are accepted, with a p-value of 0.000 < 0.05, indicating a positive and significant influence. Macroeconomic factors, such as inflation, interest rates, and exchange rates, influence financial performance ( original sample = 0.520; t-statistic = 12.350) and company size (0.212; 5.092), although they are stronger on financial performance. Capital structure shows a more dominant influence, especially on company size with a coefficient of 0.780 and a t-statistic of 8.798, illustrating the importance of leveraging leverage in company expansion. These findings conclude that macroeconomic stability and strategic capital structure management are crucial factors in supporting the performance and growth of companies in the capital-intensive healthcare industry, both during and after the pandemic.